Local Government and Poverty Alleviation in Baubau City, Indonesia - Jufri, Ardin; Nurlinah, Nurlinah; Irwan, Andi Lukman (Faculty of social and Political sciences, Hasanuddin University, 2024)
Poverty remains a multifaceted issue with economic, social, political, and cultural dimensions that significantly hinder development, particularly in Baubau City, Southeast Sulawesi, Indonesia. Despite slight fluctuations in poverty rates, persistent structural challenges limit progress in poverty alleviation efforts. This study investigates the local government's role in mitigating poverty through empowerment programs and targeted policies. Utilizing a descriptive qualitative approach, data were collected via interviews, observations, and literature reviews, analyzed thematically, and triangulated to ensure validity. The findings highlight the government's regulatory, dynamizing, and facilitative roles, supported by policies like Mayor Regulation (Perwali) of Bau-Bau City Number 13 of 2023. Strategies include reducing the economic burdens of the poor, empowering communities, and developing micro-enterprises. However, challenges such as inconsistent poverty data and infrastructural limitations persist. This study emphasizes the need for sustainable, inclusive approaches to poverty reduction and provides actionable recommendations for refining existing programs.